Discovering Malaysian state e-government maturity stage : Implementation process and progress / Mas Anom Abdul Rashid, Mohd Noor Azman Othman and Narehan Hassan - Abdul Rashid, Mas Anom; Othman, Mohd Noor Azman; Hassan, Narehan (Universiti Teknologi MARA Cawangan Pahang, 2014)
This paper is aimed to discover the current Malaysian state e-government maturity stage. The method used in this study was content analyses of 16 state government portals and websites based on the criteria given by MAMPU for the years 2007- 2013. These findings were then compared to the UN-ASPA e-Government Maturity Model to determine the current state e-government level to ensure continuous improvement is carried out in the interest of the citizens. The findings suggested that Pahang state e-government is progressing where the state government portals and websites have improved to seamless or integrated maturity level. However, the result also indicated a fluctuation in maintaining the performance of the state e-government websites.